ЗАРАЖЕННОСТЬ ГЕЛЬМИНТАМИ ЧЕРНОМОРСКОГО ШПРОТА SPRATTUS SPRATTUS PHALERICUS RISSO У БЕРЕГОВ КРЫМА - (:unkn) unknown (Севастополь: ЭКОСИ-Гидрофизика, 2005)
Приведены данные о зараженности шпрота личинками нематод Hysterothylacium aduncum и метацеркариями трематод рода Stephanostomum в различных районах шельфа Крыма (у западного, юго-западного, южного и восточного побережий – от Евпатории до Феодосии) в 1998 – 2005 гг. Отмечено отсутствие в гельминтофауне шпрота метацеркарий Nematobothrium sp. (N. scombri?); мотивировано предположение об исчезновении трематоды N. scombri из черноморской фауны. Выявлена тенденция к снижению показателей зараженности шпрота личинками H. aduncum в районе мыса Лукулл (основной промысловый район) на протяжении периода исследований. Предположительно, она обусловлена интенсивным промысловым ловом шпрота на протяжении последних лет, что привело к сдвигу возрастного состава популяции этой рыбы в сторону менее зараженных младших возрастных групп.
Helminths of the Black sea sprat Sprattus sprattus phalericus risso near the Crimean coasts
Parasitological investigation of more than 2.500 specimens of the Black Sea sprat off Eastern, Western and South-Western Crimean coasts was performed during 1998 – 2005. Two helminth species were identified; data on prevalence, intensity and abundance of nematode Hysterothylacium aduncum larvae and trematode Stephanostomum sp. in the Black Sea sprat are reported. Comparative analysis using literary data was undertaken, long-term differences in parasite fauna and indices of infection of sprat were noted. Absence of metacercaria of Nematobothrium didymozoid trematodes in helminth fauna of sprat is noted; N. scombri believed to be absent in present-day Black Sea fauna. Characteristics of sprat infectiousness with H. aduncum larvae near Cape Lukull region (Eastern Crimea coast, main Ukrainian sprat fisheries region), tend to decreasing during period of investigation. Presumably, it is a result of sprat stock over-fishing during recent years that resulted in changes of age structure of sprat population (less infected 1+ sprats become to be the most abundant age group).